RESEÑA de : McKinney, Mark (ed.): History and Politics in French-Language Comics and Graphic Novels. The University Press of Mississippi, 2008. - Fernández, Hugo (Espacio Tiempo y Forma. Serie V, Historia Contemporánea, 2015)
RESEÑA de : McKinney, Mark (ed.): History and Politics in French-Language Comics and Graphic Novels. The University Press of Mississippi, 2008.